Reconstruction of Near-Total Loss of the Upper and Lower Lips due to Purpura Fulminans with Local Tissue and a Dual-Skin Paddled Anterolateral Thigh Flap. Issue 9 (September 2017) - Kuwahara, Masamitsu; Yurugi, Satoshi; Yamanaka, Yuji; Sasaki, Chikako; Nakanishi, Takashi
Abstract : Summary: It is difficult to totally reconstruct the lip, achieving good functional and aesthetic results. There have been few reports of reconstructing complete lip defects. Moreover, upper and lower lip necrosis by purpura fulminans has not been reported. We present a case of a 60-year-old male purpura fulminans patient with upper and lower lip necrosis. Fortunately, our patient had retained his oral commissure function. We reconstructed this defect with an orbicularis oris muscle-skin-mucosal pedicled flap derived from the region between the nasolabial folds for upper lip; a similar bipedicled flap for the lower lip and the donor site was closed with a dual-skin paddled anterolateral thigh flap. Postoperative results were satisfactory, that is, no lip tightness or aperture restriction was seen, and symmetry had been achieved. The new lips exhibited complete sensory recovery. Drooling was minimal during rest and feeding. We could select a method that combined the advantages of local and free flaps. We consider our method for this defect is superior to those described in previous studies, in that the restoration of lip sensation and oral sphincter function can be achieved to some extent in 1 stage while preserving the oral commissure function. Abstract : Supplemental Digital Content is available in the text.